Formulation and Evaluation of Flurbiprofen Solid Dispersions using Novel Carriers for Enhancement of Solubility (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The main objective of the current study is to enhance the solubility and dissolution of poorlywater-soluble drug flurbiprofen, a propionic acid derivative, used as non-steroidal anti-inflammatory drug byformulating into solid dispersion (SD) employing various hydrophilic polymers as carriers in the formulation.Materials and Methods: The solubility of drug in various polymers such as AQOAT AS, PVP-K30,hydroxypropryl methyl cellulose, Soluplus, and Kollidon VA 64 was studied. Total 15 SD formulations wereprepared by solvent evaporation technique with different polymers and were evaluated for particle size analysis,% practical yield, drug content determination, and in vitro dissolution studies. Results: Based on the evaluationparameters and dissolution studies, SD6 was found to be optimized formulation. The SD6 prepared usingflurbiprofen:AQOAT AS:sodium lauryl sulfate as drug:polymer:surfactant in 1:5:2 ratios showed maximumdrug release of 99.86 in 15 min when compared with other formulation and the solubility of the formulationSD6 was enhanced 44 folds when compared to that of pure drug. Drug excipient compatibility studies wereconducted using FTIR and XRD and scanning electron microscope (SEM) studies were also conducted. FTIRstudies showed the compatibility between drug and polymers. XRD and SEM studies showed that the optimizedformulation was in amorphous form which fetched in better dissolution of the drug from the SD formulationwhen compared to the pure drug. Conclusion: This indicates the formulation technology employed with apotential of enhancing bioavailability of poorly water-soluble drug by improving its dissolution rate.